2020
DOI: 10.1038/s41565-020-0649-x
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved imaging of three-dimensional nanoscale magnetization dynamics

Abstract: The ability to experimentally map the three-dimensional structure and dynamics in bulk and patterned three-dimensional ferromagnets is essential both for understanding fundamental micromagnetic processes, as well as for investigating technologically-relevant micromagnets whose functions are connected to the presence and dynamics of fundamental micromagnetic structures, such as domain walls and vortices. Here, we demonstrate time-resolved magnetic laminography, a technique which offers access to the temporal ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 51 publications
0
96
0
Order By: Relevance
“…[ 1,2,3,12 ] The combination with recent developments in 3D magnetic characterization methods such as 3D dark‐field MOKE and 3D magnetic X‐ray imaging methods, could lead to new insights in the growing field of 3D nanomagnetism, including the development of novel applications such as high‐density storage devices and 3D logic elements. [ 38–45 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1,2,3,12 ] The combination with recent developments in 3D magnetic characterization methods such as 3D dark‐field MOKE and 3D magnetic X‐ray imaging methods, could lead to new insights in the growing field of 3D nanomagnetism, including the development of novel applications such as high‐density storage devices and 3D logic elements. [ 38–45 ]…”
Section: Discussionmentioning
confidence: 99%
“…As well as providing high spatial resolution imaging of extended systems [128], as will be discussed in Section 6, for certain α, in the laminography geometry all three components of the magnetisation are probed with one axis of rotation, therefore providing the possibility to circumvent the problems of the missing wedge associated with standard tomographic geometries. A first demonstration of magnetic laminography, and its extension to time-resolved studies of three-dimensional magnetisation dynamics, highlights the suitability for laminography as a flexible alternative to more standard magnetic tomography geometries [129]. Experimental demonstrations of the imaging of magnetisation vector fields with a,b soft X-rays and c,d hard X-rays.…”
Section: Effective Dual-axis Tomographymentioning
confidence: 99%
“…PyXL has also proven useful for measurements with magnetic contrast. Donnelly et al (2020) have demonstrated time-resolved measurements of magnetization dynamics in a microdisc using LamNI, where the laminography geometry has also proven to be advantageous compared with tomography in the ease of implementing magnetic field excitations. The spatial and temporal resolution achieved was 50 nm and 70 ps, respectively, the latter limited by the timing structure of the synchrotron source.…”
Section: Introductionmentioning
confidence: 99%